What is anatomy? - Moxham, Bernard (Henry Stewart Talks, 2019)
Anatomy: definition and derivation, The anatomical sciences, Gross anatomy, systems approach and regional approach, Basic terminology in gross anatomy, Ethics and anatomy, Different approaches to the teaching and learning of gross anatomy, The relevance of anatomy to clinical medicine, How to study gross anatomy